Let me Take the Wheel: Illusory Control and Sense of Agency. Issue 8 (August 2017) - Tobias-Webb, Juliette; Limbrick-Oldfield, Eve H.; Gillan, Claire M.; Moore, James W.; Aitken, Michael R. F.; Clark, Luke
Illusory control refers to an effect in games of chance where features associated with skilful situations increase expectancies of success. Past work has operationalized illusory control in terms of subjective ratings or behaviour, with limited consideration of the relationship between these definitions, or the broader construct of agency. This study used a novel card-guessing task in 78 participants to investigate the relationship between subjective and behavioural illusory control. We compared trials in which participants (a) had no opportunity to exercise illusory control, (b) could exercise illusory control for free, or (c) could pay to exercise illusory control. Contingency Judgment and Intentional Binding tasks assessed explicit and implicit sense of agency, respectively. On the card-guessing task, confidence was higher when participants exerted control than in the baseline condition. In a complementary model, participants were more likely to exercise control when their confidence was high, and this effect was accentuated in the pay condition relative to the free condition. Decisions to pay were positively correlated with control ratings on the Contingency Judgment task, but were not significantly related to Intentional Binding. These results establish an association between subjective and behavioural illusory control and locate the construct within the cognitive literature on agency.